2023
DOI: 10.1038/s41419-023-05585-7
|View full text |Cite
|
Sign up to set email alerts
|

PAK2 is essential for chromosome alignment in metaphase I oocytes

Abstract: As a highly conserved and ubiquitously expressed serine/threonine kinase, p21-activated kinase 2 (PAK2) participates in diverse biologic events. However, its roles in mouse oocyte meiotic maturation remain unclear. The present study revealed that mouse oocytes depleted of Pak2 were unable to completely progress through meiosis and that a majority were arrested at metaphase I. Pak2 depletion thus prompted MI arrest and induced meiotic chromosome alignment defects in mouse oocytes, in part due to a reduction in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…As reliable chromosomal separation is ensured by the bi-oriented interaction of chromosomes with the spindle through the end-on attachment of microtubules to kinetochores [ 32 ], it is conceivable that the high percentage of spindle/chromosomal defects in Net1 -depleted oocytes is a consequence of K-MT misattachments. If these attachment errors are not corrected prior to anaphase in normal oocyte maturation, they may cause chromosome-separation defects [ 16 ]; and consistent with this concept, the frequency of aneuploidy was significantly increased in Net1 -depleted oocytes relative to controls (Fig. 4 C).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…As reliable chromosomal separation is ensured by the bi-oriented interaction of chromosomes with the spindle through the end-on attachment of microtubules to kinetochores [ 32 ], it is conceivable that the high percentage of spindle/chromosomal defects in Net1 -depleted oocytes is a consequence of K-MT misattachments. If these attachment errors are not corrected prior to anaphase in normal oocyte maturation, they may cause chromosome-separation defects [ 16 ]; and consistent with this concept, the frequency of aneuploidy was significantly increased in Net1 -depleted oocytes relative to controls (Fig. 4 C).…”
Section: Discussionmentioning
confidence: 64%
“…These phenotypes contrasted sharply with control oocytes that exhibited a typical barrel-shaped spindle and well-aligned chromosomes at the cellular equator. In order for chromosomes to be properly aligned and segregated, kinetochores must be attached to microtubules emanating from the opposite spindle pole [ 16 ]; however, we noted that Net1 -KD oocytes exhibited spindle/chromosome disorganization and hypothesized that NET1 may be required for correct kinetochore-microtubule (K-MT) assembly. CREST was used to detect kinetochores, anti-α-tubulin antibody was used to visualize spindles, and Hoechst 33,342 was used to visualize chromosomes in MI oocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous reports, METTL3 function as tumor-promoting factors in many cancer types or METTL3 inhibiting hinders tumor growth cancer growth, etc. liver cancer (HepG2) and cervical cancer (HeLa) [24] ; colorectal cancer (HCT116) [25] ; leucocythemia (CCRF-CEM, K562, MDSL, HL60) [14] , PCa cell(DU145, PC3) [26] .The results showed that both RSM3 and RM3 exhibited broad toxicity towards various cancer cells including PC3, DU145, HeLa, HepG2, HCT116, A549, K562, MDS-L, CCRF-CEM ( Fig. S8 ).…”
Section: Resultsmentioning
confidence: 99%